The Objectives of TIMS - Flood, Merrill M. (Management Science, 1956)
Article II of the Constitution of The Institute of Management Sciences provides that: “The objects of The Institute shall be to identify, extend, and unify scientific knowledge that contributes to the understanding and practice of management.” This evening, I shall offer a few personal views and convictions concerning possible paths through the future to these goals.